Unilateral Cysticercosis of the Parotid Gland: Case Report, Diagnosis, and Clinical Management - Elwell, Zachary; Bearelly, Shethal; Aboul-Nasr, Khalid; Lara, Jonathan (Case Reports in Otolaryngology, 2021)
Cysticercosis is a systemic parasitic infection caused by the establishment of the larval form of the parasitic cestode, Taenia solium. Cysticercosis is acquired via the fecal-oral route and is prevalent in low- and middle-income countries (LMICs). Patients typically manifest with skeletal muscle, subcutaneous, or central nervous system involvement. Though there are reports of oral mucosa involvement, solitary involvement of the parotid gland is rare. This is a rare case of a 57-year-old man diagnosed with parotid cysticercosis by imaging and FNA. He was successfully treated by anthelminthic therapy and needle aspiration. The patient has been seen back several times. The cyst is not palpable, and he is satisfied. Parotid cysticercosis should be considered in the differential of a parotid mass in patients who have traveled to endemic regions. Though prior reports have indicated the importance of surgical excision, this patient was treated medically.